PENGARUH SENAM OTAK TERHADAP TINGKAT KONSENTRASI BELAJAR SISWA - Fauziah Ramadani; Sisca Oktarini; Rista Nora (LPPM Universitas Abdurrab, 2025)
ABSTRACT Difficulty concentrating is experienced by many adolescents, especially in the learning process. Brain exercise is a series of simple movements designed to stimulate the optimization of the work of the brain. The purpose of this study was to determine the effect of brain exercise on the level of learning concentration of class XE3 students at SMAN 2 Payakumbuh City. The population in this study is class XE3 at SMAN 2 Kota Payakumbuh with 36 students. The sample used it 15 respondents with a sampling technique of purposive sampling. This study uses a pre experimental design with One Group Pre and Post Test Design, which uses a treatment group and without using a control group. The results were found that the mean pre test (4.93) and post test (10.40) experienced an increase in concentration with a value of P=0,000. The results showed that there were differences in the level of concentration before being given brain exercise and after being given brain exercise. Thus the brain gymnastics can be used as a method to increase student concentration in learning so that the goal of learning can be achieved.